MicroRNA and circular RNA profiling in the deposited fat tissue of Sunite sheep - He, Xige; Wu, Rihan; Yun, Yueying; Qin, Xia; Huang, Yajuan; Chen, Lu; Han, Yunfei; Wu, Jindi; Sha, Lina; Borjigin, Gerelt (Frontiers in Veterinary Science, 2022)
As the most typical deposited fat, tail fat is an important energy reservoir for sheep adapted to harsh environments and plays an important role as a raw material in daily life. However, the regulatory mechanisms of microRNA (miRNA) and circular RNA (circRNA) in tail fat development remain unclear. In this study, we characterized the miRNA and circRNA expression profiles in the tail fat of sheep at the ages of 6, 18, and 30 months. We identified 219 differentially expressed (DE) miRNAs (including 12 novel miRNAs), which exhibited a major tendency to be downregulated, and 198 DE circRNAs, which exhibited a tendency to be upregulated. Target gene prediction analysis was performed for the DE miRNAs. Functional analysis revealed that their target genes were mainly involved in cellular interactions, while the host genes of DE circRNAs were implicated in lipid and fatty acid metabolism. Subsequently, we established a competing endogenous RNA (ceRNA) network based on the negative regulatory relationship between miRNAs and target genes. The network revealed that upregulated miRNAs play a leading role in the development of tail fat. Finally, the ceRNA relationship network with oar-miR-27a_R-1 and oar-miR-29a as the core was validated, suggesting possible involvement of these interactions in tail fat development. In summary, DE miRNAs were negatively correlated with DE circRNAs during sheep tail fat development. The multiple ceRNA regulatory network dominated by upregulated DE miRNAs may play a key role in this developmental process.